Upaya Penurunan Prokrastinasi Akademik Siswa Melalui Pelatihan Time Management - Nuriah Halleyda; Siti Shalma Fitriah; Ghea Aziza Motik; Yudhi Satria (Universitas Muhammadiyah Surakarta, 2022)
The transition period of the online learning process from home creates an imbalance in school life and creates conditions of academic delay or procrastination among students. Based on previous research on 345 students at SMP Negeri 2 Jatisrono in February 2022, the results of student academic procrastination at the school were quite high. This community service activity aims to reduce the high level of student academic procrastination through time management training. The training was attended by 31 students at SMP Negeri 2 Jatisrono. The instrument used to measure the level of student academic procrastination is the academic procrastination scale. Measurements were carried out 2 times, namely before (pre test) and after (post test) training to determine the effectiveness of time management training in reducing the level of academic procrastination experienced by students. The results of data analysis using T-test showed a score of t = 40.83 with p = 0.000 (p <0.05), which means that there is a very significant decrease in academic procrastination after receiving time management training. In conclusion, time management training is very significantly effective in reducing academic procrastination in students at SMP Negeri 2 Jatisrono. Suggestions for further research is that this kind of training can be applied to other problems because it is able to reduce forms of negative behavior so that it can optimize learning outcomes and student achievement.